The Relation Between Corporate Water Risk, Water Accounting and Financial Performance of Metal Mining Firms - Raj, Arun (University of Waterloo, 2016)
Water is increasingly being recognized as a scarce resource. Water intensive industries such as mining are progressively realizing the need and importance to judiciously and efficiently manage their water requirements. Water scarcity is a noticeable factor influencing corporate growth and performance. Although water sustainability initiatives are known to have an overall positive impact on corporate performance, there is little information on its impact on corporate financial performance. This study focuses on business risk associated with water in metal mining industry and its impact on corporate water and financial performance. In this study a sample of 20 metal mining corporations corresponding to 244 active mines, that are a member of International Council of Metals and Mining (ICMM) were used to analyze 1) the relation between water risk and corporate water performance and 2)the relation between water performance (non-financial) and financial performance of companies? The results indicate a positive correlation between water risk and corporate water performance. Furthermore, the results did not indicate a strong correlation between water performance and financial performance of companies
Keywords: water security; water resources development; mining corporations; water use; mining; corporation reports; social responsibility of business